Krisis Identitas Nasional: apakah campur kode merupakan ancaman bagi bahasa Indonesia? - Feni Verawati; Nisa Nurmaulida Tsani; Siska Gandari; Achmad Syauky; Azmi Muhammad Dahlan; Rama Wijaya Abdul Rozak; Nisrina Nurul Insani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research aims to investigate whether code-mixing poses a threat to the Indonesian language as the national identity and the efforts that can be done as a prevention of identity crisis. It is because society is beginning to forget its national language. The research method used is descriptive qualitative. The research data were obtained from the general public who mix languages in their daily communication. Data collection was conducted by distributing questionnaires to respondents through Google Forms. The data obtained will then go through several stages, including data tabulation, description, and analysis. From the results obtained from this study, approximately 68.3% of the respondents mix their local and foreign languages with the Indonesian language. This frequent code-mixing can pose a threat to national identity, as people tend to forget their language and feel proud when using foreign languages. However, it was also found that code-mixing positively impacts social and cultural aspects, as it can be used to communicate more effectively and as a means of learning new languages. Code-mixing can become a threat if the speaker consciously prefers to use a foreign language in a conversation.